Capturing the complexity: Towards a better understanding of collaborative higher education provision in the UK - Mariampillai, John (Advances in Social Sciences Research Journal, 2021)
This article investigates collaborative Higher Education (HE) landscape in the United Kingdom (UK). Collaborative arrangements between publicly funded (i.e. with recurrent funding from the Funding Councils or other public bodies) Higher Education Institutions (HEIs) and other private providers have witnessed a significant expansion since 2010, in terms of student numbers and public-backed student loan support. The focus of this article is on understanding the rationale and complexities around collaborative HE provision involving HEIs and other private providers. This article uses data collected through interviews, involving 19 stakeholders representing collaborative HE provision in the UK.